The Impact of energy utilization on environment - Hawlader, Mohammad Nurul Alam (IIUM Press, 2011)
Energy and environment, both arc essential for our survival on the planet earth to ensure a deeem standard of living and good health. However, there is a price [or the comfort that we strive hard to achievc. It took forty years to realize that CFC (Chlorofluorocarbons) causes Ozone depletion. Similarly. greenhouse gases and acid rain are realities that we have to contain to provide a cleaner environment [or the future generation. Fossil fuels are essential but their application can be limited to areas where high temperatures are required. For power production, natural gas should be encouraged. Solar thermal applications may be considered for areas where low temperatures are involved, as the technology is proven.